2017
DOI: 10.1002/cphc.201700579
|View full text |Cite
|
Sign up to set email alerts
|

Direct Carbonation of Glycerol with CO2 Catalyzed by Metal Oxides

Abstract: Five metal oxides (ZnO, SnO2, Fe2O3, CeO2, La2O3) were produced by the sol–gel method and tested in the direct carbonation of glycerol with CO2. Initial tests with Fe2O3 showed that the best reaction condition was 180 °C, 150 bar, and 12 h. The other oxides were evaluated at these conditions and were all active to the formation of glycerol carbonate. Zinc oxide was the most active catalyst, with a yield of 8.1 % in the organic carbonate. The catalytic activity decreased upon washing and drying the ZnO catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 41 publications
(53 reference statements)
1
15
0
Order By: Relevance
“…Up to now, many catalytic systems have been reported that are based on metal oxides/complexes, [52][53][54][55][56][57] supported metal catalysts, 58,59 or modified zeolites or hydrotalcites, [60][61][62] in combination with a dehydrating reagent. Most of the reported heterogeneous catalysts typically require harsh reaction conditions for GC synthesis, i.e.…”
Section: Glycerol Carbonate From Glycerol and Comentioning
confidence: 99%
“…Up to now, many catalytic systems have been reported that are based on metal oxides/complexes, [52][53][54][55][56][57] supported metal catalysts, 58,59 or modified zeolites or hydrotalcites, [60][61][62] in combination with a dehydrating reagent. Most of the reported heterogeneous catalysts typically require harsh reaction conditions for GC synthesis, i.e.…”
Section: Glycerol Carbonate From Glycerol and Comentioning
confidence: 99%
“…In order to overcome thermodynamic limitations, basic dehydrating agents can be used to remove water and shift the equilibrium to the product side. In the absence of dehydrating agents, the reaction achieves only low yields, e.g., over metal impregnated zeolites, at 100 bar, a 6% yield of glycerol carbonate was achieved [22]; while an 8% yield of glycerol carbonate was observed upon the introduction of ZnO at 150 bar [23]. Higher yields have been achieved when conducting the reaction in methanol as a solvent, with George and co-workers observing a 35% yield at 138 bar [24].…”
Section: Introductionmentioning
confidence: 99%
“…Under certain reaction conditions, both CO 2 and CO can be used as carbonylation reagents to react with glycerol to generate GC, but compared with CO 2 , CO has higher chemical activity. In the reaction of glycerol and CO to produce GC, the most common oxidant is oxygen, which can afford GC in high yield under relatively mild conditions [52].…”
Section: Co Oxidative Carbonylation Routementioning
confidence: 99%